Development of Metal Carbonate-based Nano- and Micro-structural Composite Materials - Ghariani, Munirah (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2026)
The main aim of this work was to develop a wide range of metal carbonate-based composite materials, investigate their properties and explore their potential applications. These materials were synthesised employing various approaches, including a novel dry ice carbonation. Chapter 1 presents a necessary background and an overview of the literature that is relevant to the research presented in this thesis. This involves a preliminary introduction to nanomaterials and their diverse applications, emphasizing their unique physiochemical properties that greatly differ from their bulk counterparts. Particular attention is then given to the nucleation and growth of calcium carbonate due to its polymorphic forms and adaptable functionality, followed by the preparation methods employed to develop the carbonate-based materials. The discussion further covers magnetism and chirality at a nanoscale level, highlighting their impact on material properties and potential applications. Lastly, this section encompasses photoluminescence and the development of multimodal composites. Chapter 2 describes all the experimental work carried out in this thesis, including the experimental methods and procedures for each section. This chapter also provides a detailed description of the instrumental techniques used to characterise the materials prepared in this work. Chapter 3 presents the development of magnetic calcium carbonate-based composites. These materials have been synthesised using a novel dry ice carbonation approach, both in aqueousand in solvent-free conditions. New multifunctional microstructures comprising of a magnetite core, a layer of a negatively charged polyelectrolyte followed by the incorporation of calcium carbonate were developed. It presents the synthesis and characterisation of the two materials followed by their loading and release studies using a cationic dye. Chapter 4 reports the synthesis of bare and PSS stabilised magnetic NPs using a coprecipitation technique. Subsequently, the precipitation of sodium carbonate and calcium chloride was used to introduce calcium carbonate into the magnetic system. Several distinct magnetic multimodal composite materials were successfully synthesised and systematically characterised. Chapter 5 focuses on the development of different types of chiral microstructures. The first part involved the synthesis of chiral magnetic calcium carbonate composites using the coprecipitation technique and TA as the ligand. The materials were fully characterised, and their loading capacity was tested for targeted drug delivery applications. The novel dry ice carbonation was used to develop chiral structures using TA and mandelic acid in the absence of magnetic NPs. The chiral ligands were found to play a significant role in directing polymorph growth and phase selection of calcium carbonate. Chapter 6 details the synthesis of four different metal carbonates utilising the novel dry ice carbonation approach. Namely, these were magnesium, copper, terbium and europium carbonates. These carbonates were fully characterised by various instrumental techniques. Finally, chapter 7 is the concluding section which highlights the main achievements of this body of research. It also offers an outline for future work building on the research objectives achieved in this thesis.
APPROVED